2018
DOI: 10.1080/10410236.2018.1548335
|View full text |Cite
|
Sign up to set email alerts
|

Are We Making Progress on Communication with People Who Are Near the End of Life in the Australian Health System? A Thematic Analysis

Abstract: Initiating end-of-life discussions with patients is often delayed or avoided altogether by health care practitioners even in light of imminent death. This continues despite the availability of guidelines and conceptual frameworks on how to communicate prognoses at end-of-life. We surveyed health care practitioners to elicit their exposure to and confidence in end-of-life discussions and to better understand factors that enable or challenge the initiation of discussions in Australian health care settings. Thema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Another challenge to apply our findings involves the time required to engage in the complex and sensitive conversations that our participants described. Consistent with previous research, participants felt that time pressure poses a barrier to engaging in these conversations ( 24 , 25 ). They identified that in Australian primary healthcare, longer consultations are not as well remunerated as high-throughput medicine.…”
Section: Discussionsupporting
confidence: 74%
“…Another challenge to apply our findings involves the time required to engage in the complex and sensitive conversations that our participants described. Consistent with previous research, participants felt that time pressure poses a barrier to engaging in these conversations ( 24 , 25 ). They identified that in Australian primary healthcare, longer consultations are not as well remunerated as high-throughput medicine.…”
Section: Discussionsupporting
confidence: 74%
“…This research highlights that, in practice, recruitment to a rapid autopsy programme is both an art and a science, and certainly not a ‘one-size-fits-all’ scenario. 5,6 In general, it appears that the approaches taken by the CASCADE team are acceptable to patients who have consented to the programme.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 There is also recognition that end-of-life communication can be emotionally burdensome for practitioners and that there is not a one-size-fits-all approach to discussing a terminal prognosis with patients. 5,6 However difficult discussions can be successfully negotiated by developing trusting relationships and rapport with patients and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement with, and completion of, ACP documents is influenced by cultural factors [6]. In Australia, ACP conversations can be emotionally challenging for both patients and practitioners but are of great value [7].…”
Section: Introductionmentioning
confidence: 99%